Bioinformatic analysis and clinical diagnostic value of hsa_circ_0004099 in acute ischemic stroke - Zheng, Jiqing; Luo, Shuiming; Long, Yaobin (PloS one, 2022)
This study investigates the expression and effect of hsa_circ_0004099 in acute ischemic stroke (AIS). We conducted a case-controlled study that included 40 patients with AIS within 24 hours and 40 healthy subjects during the same period as a control group. Differentially expressed circular RNAs (circRNAs) were obtained using GEO2R, and the expression of hsa_circ_0004099 was verified using RT-PCR. Correlation analysis of the National Institutes of Health Stroke Scale (NIHSS) disease severity score and ischemic time with hsa_circ_0004099 expression levels was also performed. The receiver operating characteristic (ROC) curve of hsa_circ_0004099 was constructed, and bioinformatic analysis of hsa_circ_0004099 was performed. NIHSS scores negatively correlated with hsa_circ_0004099 levels (P<0.001, r = -0.7053), whereas infarct time was negatively correlated with hsa_circ_0004099 levels (P<0.001, r = -0.5130); hsa_circ_0004099 could benefit clinical diagnosis (area under the curve [AUC]: 0.923 [95% confidence interval [CI]: 0.8680–0.9904]). Kyoto encyclopedia of genes and genomes (KEGG) analysis showed that hsa_circ_0004099 was enriched in several cancer pathways, which were collectively enriched in four genes namely TCF7L2, NRAS, CTNNB1, and KRAS. Eight core proteins were screened using a protein-protein interaction (PPI) network namely SMAD4, HIF1A, CTNNB1, CDKN1B, CDK6, FOXO3, KRAS, and NRAS. hsa_circ_0004099 is a potential clinical diagnostic marker. In addition, the possible role of hsa_circ_0004099 in the pathogenesis of AIS was analyzed using bioinformatics, which provided a new potential molecular target for AIS treatment.